Sistem Pendukung Keputusan Seleksi Penerimaan Panitia Pemilihan Kecamatan Menggunakan Weighted Product Di KPU Kabupaten Sukabumi - Firmansyah, Rian (Universitas Muhammadiyah Riau, 2023)
2024 will be an important year in the history of democracy in Indonesia, as the general election will be held that year to determine the new face of the government. Therefore, this election activity involves many parties, including the General Election Commission (KPU). To carry out all of these tasks efficiently, the KPU requires the support of many supporting personnel. In preparation for this election, the KPU held a selection of the Election Committee (PPK) reception, especially the KPU of Sukabumi Regency. In determining the candidate employees who will be accepted as PPK in each previous event, they still use manual methods, which reduce the effectiveness in choosing candidate employees. One solution to overcome this problem is to require a personnel recruitment decision support system that can facilitate the Sukabumi Regency KPU in determining the candidate employees who will be accepted according to the predetermined criteria. Based on the explanation above, the results of this study are that the Sukabumi Regency KPU has a decision support system application for the selection of PPK reception using the weighted product method.